Influence of Packaging Element on Beverage Product Marketing - Purwaningsih, Isti; Surachman, Surachman; Pratikto, Pratikto; Santoso, Imam (International Review of Management and Marketing, 2019)
This research aims to discover the influence of packaging elements on consumers' purchase intention towards beverage products that use PET bottles. There are three methods to rate product packaging (image tests, usage test, and visibility tests). The results show that the model generated is only able to explain 39.2% of the variance. The visual element of packaging is the most significant influence on consumers' purchase intention. There are two significant indicators that influence the visual variable (bottles with different colors and shape attractiveness), and shape distinctiveness is the indicator that best describes the visual variable. This research combines of three methods to rate product packaging (image tests, usage test, and visibility tests). Keywords: Beverage products, informational packaging, PET package bottle, verbal elements, visual appearance, visual packaging JEL Classifications: M110, M310, M370 DOI: https://doi.org/10.32479/irmm.8831